A patient with HIV infection presenting with diffuse membranous glomerulonephritis in a country with a low HIV prevalence-remarkable remission with therapy - Aydın, Selda; Mete, Bilgül; Yılmaz, Mesut; Yenidünya, Gülşah; Zaras, Reşat; Tunçkale, Aydın; Tabak, Fehmi (My University, 2012)
The most common manifestation of HIV in the kidney is HIV-associated nephropathy (HIVAN). In this report, we describe the first documented case of membranous glomerulonephritis in an HIV-positive individual in Turkey, the country with the lowest HIV prevalence in the region. The case occurred in an HIV-positive, hepatitis C (HCV)-negative, and hepatitis B (HBV)-negative Caucasian male, who presented with nephrotic-range proteinuria. The patient had a favorable response to HAART and an angiotensin-receptor blocker.
Keywords: HIV; Membranous Glomerulonephritis; Nephropathy